How Does AirAsia Survive From the COVID-19 Pandemic? - Kuek, Thiam Yong; Quttainah, Majdi Anwar; Wong, Yung Ting; Wong, Kim Fong; Wu, Kejian; Wu, Minli (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
This paper aims to discover the financial issues the company faced and their implications for its marketing and operation management. The researchers use a qualitative method to conduct the study. The researchers also conducted an in-depth SWOT analysis to identify the opportunities the company could seize. This paper has a detailed discussion of the strategies and decisions the company implemented, such as Teleport, e-hailing service, and food delivery. From the analysis, the researchers find that the company could seize the opportunities via marketing and operation strategies based on its own strengths and weaknesses. AirAsia makes an alternative such as e-commerce, logistics, and food delivery which has catered to overwhelming customer demand and supports the critical need to transport medical aid and necessity goods in response to the global pandemic. As well as control costs during the COVID-19 pandemic is an important factor to keep AirAsia surviving. Keywords: AirAsia, Business Solutions, COVID-19, Management Issue, Marketing Problems, Operation Problems, Recommendations.